Solving an optimal route for tourist at Langkawi using heuristics technique - Hashim, Zakiah; Mat Desa, Wan Laailatul Hanim; Aziz, Hurul Ain; Mohd Zaki, Nur Mariana Zaimah (2018)
Tourism is an important industry for this country because it is one of a major contributor to the economics of Malaysia.In this paper, we focus Langkawi Island as the case study because normally, tourist travel to Langkawi Island will drive the rented car as the primary mode of transport.Thus, the aim of this paper is to develop a mathematical modelling to find an optimal route for tourist to travel to their interesting places around Langkawi Island. Heuristic technique was applied in this study which emphasized on several greedy heuristic methods in order to solve the problem.MATLAB version 7.8 has been used to get the solution for all greedy heuristic method.The result obtained shows that nearest greedy method gives better result compared to the nearest greedy insertion method.The minimum value of the route selection gives effect to the cost of travelling.Therefore, from this study, the best route that connect from one interesting place to others place can be suggested to the tourist as a guidance.In addition, tourist can save their time and money to pay for tourist guide.